2018
DOI: 10.1155/2018/7259146
|View full text |Cite
|
Sign up to set email alerts
|

The Ethnopharmacological and Nutraceutical Relevance of Launaea taraxacifolia (Willd.) Amin ex C. Jeffrey

Abstract: Launaea taraxacifolia (Willd.) Amin ex C. Jeffrey is a herb found mostly in tropical Africa. The plant, commonly found in West Africa, is used in the management of many diseases including cardiovascular, respiratory, haematological, endocrine, and metabolic diseases in Ghana, Nigeria, Benin, Serra Leone, and Senegal. This piece provides comprehensive and updated information on the traditional uses, phytochemical constituents, and pharmacological and toxicological information available on Launaea taraxacifolia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We have previously reported the chemical characterization, antioxidant and phytotoxic activities of essential oils of three Launaea plants including L. nudicaulis [ 10 ]. Due to the history of the genus in addition to the potent biological activities of L. nudicaulis especially, antioxidant potentiality, existing evidence suggested that it has potential antidiabetic activity [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the chemical characterization, antioxidant and phytotoxic activities of essential oils of three Launaea plants including L. nudicaulis [ 10 ]. Due to the history of the genus in addition to the potent biological activities of L. nudicaulis especially, antioxidant potentiality, existing evidence suggested that it has potential antidiabetic activity [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are produced from mevalonic acid (MVA), which is the primary source of the active isoprene unit isopentenyl diphosphate, which is a unit of isoprene. The variety of volatile components in this structure has drawn researchers and experts to investigate their significance in relation to industrial and biological activities [6,7]. Throughout history and in all cultures, aromatic herbal plants have been extensively medicinally used to prevent, treat, and control a wide range of ailments [5,[8][9][10].…”
Section: To Reduce Tension One Can Massage Aromatherapeuticmentioning
confidence: 99%
“…Launaea taraxacifolia has a medicinal capability (Borokini & Labumi, 2017) as a result of its phytochemical constituents, and pharmacological potency which is useful in eliminating migraine, in treating conjunctivitis (Sakpere & Aremu, 2008). African lettuce helps to treat urinary tract problem, diabetes mellitus (Adinortey et al, 2018), in preventing whooping cough and to increase the production of milk by feeding the lactating cows (Bello et al, 2018). It can be incorporated in our daily diet either by mixing it with salad or cooking with sauce or soups (Sakpere & Aremu, 2008).…”
Section: Introductionmentioning
confidence: 99%